2014
DOI: 10.1111/jfb.12310
|View full text |Cite
|
Sign up to set email alerts
|

Acid–base and ion balance in fishes with bimodal respiration

Abstract: The evolution of air breathing during the Devonian provided early fishes with bimodal respiration with a stable O2 supply from air. This was, however, probably associated with challenges and trade-offs in terms of acid-base balance and ionoregulation due to reduced gill:water interaction and changes in gill morphology associated with air breathing. While many aspects of acid-base and ionoregulation in air-breathing fishes are similar to water breathers, the specific cellular and molecular mechanisms involved r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 78 publications
2
53
0
Order By: Relevance
“…This reveals a pronounced capacity for metabolic pH e regulation during hypercapnia in P. hypophthalmus. This is in stark contrast to all other air-breathing fishes studied to date that have a low capacity for pH e regulation during a respiratory acidosis (Shartau and Brauner, 2014). Thus, the armored catfish Liposarcus pardalis only recovered 8% and 22% of the pH e disturbance when exposed to ∼7 mmHg CO 2 and 42 mmHg CO 2 , respectively for 96 h (Brauner et al, 2004).…”
Section: Results and Discussion Acid-base Regulation During Hypercapniamentioning
confidence: 66%
See 1 more Smart Citation
“…This reveals a pronounced capacity for metabolic pH e regulation during hypercapnia in P. hypophthalmus. This is in stark contrast to all other air-breathing fishes studied to date that have a low capacity for pH e regulation during a respiratory acidosis (Shartau and Brauner, 2014). Thus, the armored catfish Liposarcus pardalis only recovered 8% and 22% of the pH e disturbance when exposed to ∼7 mmHg CO 2 and 42 mmHg CO 2 , respectively for 96 h (Brauner et al, 2004).…”
Section: Results and Discussion Acid-base Regulation During Hypercapniamentioning
confidence: 66%
“…However, the gills of airbreathing fishes are generally reduced in size -an adaptation that is presumed to aid in avoiding branchial O 2 loss in hypoxic water -but have retained their ancestral function in acid-base and ion regulation (Graham, 1997;Tamura and Moriyama, 1976). It has therefore been suggested that the reduced surface area of the gills of air-breathing fishes places limitations on transepithelial ion exchange, thus constraining the branchial capacity for acid-base regulation (Brauner and Baker, 2009;Shartau and Brauner, 2014). Therefore, all studies on acid-base regulation in air-breathing fishes to date indicate a low capacity for exchange of acid-base equivalents in pH e regulation and a preferential regulation of intracellular pH, during a respiratory acidosis (Brauner and Baker, 2009;Brauner et al, 2004;Harter et al, 2014b;Heisler, 1982;Shartau and Brauner, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Impaired O 2 transport can also occur via the Root effect: a phenomenon found only in fishes, which prevents Hb from becoming fully O 2 saturated at high P CO 2 (Root and Irving, 1941;Gillen and Riggs, 1971). It has been hypothesized that welladapted air-breathing and amphibious fishes should possess relatively pH-insensitive Hb to reduce the consequences of Bohr and Root effects on O 2 transport (Graham, 1997;Shartau and Brauner, 2014); however, not all air-breathing fishes follow this pattern (e.g. Farmer et al, 1979;Wells et al, 1997).…”
Section: Received 4 July 2014; Accepted 15 September 2014mentioning
confidence: 99%
“…That exercise, like increased temperature, did not induce air breathing might indicate that hypoxic stimulation of external rather than internal O 2 receptors is needed to initiate air breathing. It could also be an adaptive strategy that lowers the risk of aerial predation at a time when the fish has little capacity left for anaerobic burst swimming and thus escape responses, while also facilitating excretion of CO 2 (Shartau and Brauner, 2014). It would be interesting to investigate whether hypoxia restricts sustained swimming performance in Alaska blackfish, as observed in the banded knifefish (Gymnotus carapo) (McKenzie et al, 2012).…”
Section: Exhaustive Exercise and Aerobic Scopementioning
confidence: 99%